A Flexible Caterpillar‐Like Gold Nanoparticle Assemblies with Ultrasmall Nanogaps for Enhanced Dual‐Modal Imaging and Photothermal Therapy. Issue 19 (14th April 2018) - Xia, Yuanzhi; Ma, Xuehua; Gao, Junhua; Chen, Guoxin; Li, Zihou; Wu, Xiaoxia; Yu, Zhangsen; Xing, Jie; Sun, Li; Ruan, Huimin; Luo, Lijia; Xiang, Lingchao; et al.
Abstract: Gold nanoparticle (AuNP) assemblies (GNAs) have attracted attention since enhanced coupling plasmonic resonance (CPR) emerged in the nanogap between coupling AuNPs. For one dimensional GNAs (1D‐GNAs), most CPR from the nanogaps could be easily activated by electromagnetic waves and generate drastically enhanced CPR because the nanogaps between coupling AuNPs are linearly distributed in the 1D‐GNAs. The reported studies focus on the synthesis of 1D‐GNAs and fundamental exploration of CPR. There are still problems which impede further applications in nanomedicine, such as big size (>500 nm), poor water solubility, and/or poor stability. In this study, a kind of 1D flexible caterpillar‐like GNAs (CL‐GNAs) with ultrasmall nanogaps, good water solubility, and good stability is developed. The CL‐GNAs have a flexible structure that can randomly move to change their morphology, which is rarely reported. Numerous ultrasmall nanogaps (<1 nm) are linearly distributed along the structure of CL‐GNAs and generate enhanced CPR. The toxicity assessments in vitro and vivo respectively demonstrate that CL‐GNAs have a low cytotoxicity and good biocompatibility. The CL‐GNAs can be used as an efficient photothermal agent for photothermal therapy, a probe for Raman imaging and photothermal imaging. Abstract : Ultrasmall nanogaps in caterpillar‐like gold nanoparticle assemblies (CL‐GNAs) bring enhanced coupling plasmonic resonance that determines enhanced near‐infrared absorption of CL‐GNAs. Furthermore, the 1D flexible structure of CL‐GNAs allows for easy interaction with the excitation of electromagnetic waves. Based on their unique optical property, CL‐GNAs play an important role in the photothermal therapy and dual‐modal imaging of tumors.